Childhood Factors and Incarceration for African American Men: How Early Life Community Experience Influences Adult Outcomes - Cobb, Abigail (2016)
There is a dearth of research that analyzes childhood influence on adult incarceration, and an associated lack of emphasis on the relationship between childhood poverty, lack of educational attainment, and family structure on criminality among African American men – a population wherein individuals are both incarcerated and generally socioeconomically disadvantaged at disproportionately higher rates. Consistent with the recent demand for criminal justice reform, the need for systematic research pertaining to tendencies in criminality has become apparent. Resulting from secondhand statistical data analysis on aggregate state factors such as childhood poverty rate, rate of single-parenthood, and high school drop out rate, the intention of this study is to fill the existing void through examination of the effects of these childhood familial conditions on incarceration in adulthood among African American men